Anonymous Location Tracking for Privacy and Preservation - Sujitha, Karlapalem; Suhasini, R.; Teja, B. Charan; Kavya, P.; Varun, M. (2025 5th International Conference on Pervasive Computing and Social Networking (ICPCSN), 2025)
In an era where location-based services (LBS) are integral to daily life, protecting user privacy has become a pressing concern. This study introduces an anonymous location tracking system designed to safeguard user data while ensuring the continued functionality of LBS. This project presents a privacy-presenting location-tracking system utilizing HTML, CSS, Java Script, Chrome Extension APIs, Manifest V3, Dev Tools, and DOM Events (Custom Events) to enable secure and anonymous geospatial data handling. The system ensures user anonymity by implementing location obfuscation and anonymization techniques while maintaining service accuracy. Leveraging Chrome Extension API's and Manifest V3, it provides seamless integration with the browser environments, enabling efficient real-time location tracking. The use of Custom Events enhances inter activity with in DOM, allowing dynamic communication between system components. By combining modern web technologies with privacy-centric approaches, this project offers an innovative and practical framework for ethical geolocation data management.Objective: This project aims to develop a privacy-preservation location-tracking system using HTML, CSS, JavaScript, Chrome Extension APIs, Manifest V3, and Dev Tool's to ensure secure and anonymous geospatial data handling. It leverages DOM Events (Custom Events) to enhance real time interactions. The system is designed to be scalable, reliable, and adaptable for various location-based applications.